O bem-dito sertão: as veredas de lalíngua em Guimarães Rosa - Cançado, Marina Junqueira (2020)
The present work aimed to discuss how the practice of the lyrics of Guimarães Rosa in his novel Grande Sertão Veredas allows the concept of lalangue to emerge, forged by Jacques Lacan. For this discussion, initially, the path of Freud and Lacan with literature and how they take it as an emergency of the unconscious in its functioning will be highlighted. Refusing to adopt the posture of an external field that analyzes art, the work developed here aims to establish as the literary work, as a rest of unconscious formation that allows psychoanalysis itself to emerge. As a second point, the work focuses on the concept of lalangue, its unfolding for psychoanalytic theory and its evident connection with poetic literature, which opens up a lack of knowledge, a breakdown of meaning and leaves a hole in the language that is lalangue itself. Finally, the braid is linked to the lyrics of the narrative undertaken by Guimarães Rosa as a subversion of the language that enables the emergence of one language, among others, lalangue as proposed by Lacan. The neologisms, onomatopoeia and other figures of speech placed in the narrative of the backcountry Riobaldo make the crack that breaks the meaning, overflowing another language, lalangue, full of joy and resistant to any attempt at apprehension.